A note on conspicuous leisure, animal spirits and endogenous cycles - Weder, Mark (2018)
This paper investigates general equilibrium effects of conspicuous leisure. It finds that leisure externalities reduce the degree of other market im- perfections needed to generate indeterminacy or sunspot equilibria – endogneous cycles become empirically more plausible. Sunspot equilibria are possible with a downward-sloping labor demand schedule. The economic reasoning behind the result is that with conspicuous-externalities, labor is drawn more easily in and out of leisure to help fulfill agents’ expectations.